Terpenes: Effect of lipophilicity in enhancing transdermal delivery of alfuzosin hydrochloride - Prasanthi, D. (Medknow Publications & Media Pvt Ltd, 2012)
Transdermal drug delivery has attracted much attention as an alternative to intravenous and oral methods of delivery. But the main barrier is stratum corneum. Terpenes classes of chemical enhancers are used in transdermal formulations for facilitating penetration of drugs. The aim of the study is to evaluate terpenes as skin penetration enhancers and correlate its relationship with permeation and lipophilicity. In this study, alfuzosin hydrochloride (AH) hydrogels were prepared with terpenes using Taguchi orthogonal array experimental design. The formulations contained one of eight terpenes, based on their lipophilicity (log P 2.13-5.36). The percutaneous permeation was studied in rat skin using diffusion cell technique. Flux, cumulative amount, lag time and skin content of AH were measured over 24 hours and compared with control gels. Nerolidol with highest lipophilicity (log P 5.36 ± 0.38) showed highest cumulative amount (Q(24)) of 647.29 ± 18.76 μg/cm(2) and fluxrateof 28.16 ± 0.64 μg/cm(2)/hour. It showed decreased lag time of 0.76 ± 0.15 hours. Fenchone (2.5%) (log P 2.13 ± 0.30) produced the longest lag time 4.8 ± 0.20 hours. The rank order of enhancement effect was shown as nerolidol > farnesol > limonene > linalool > geraniol > carvone > fenchone > menthol. Lowest skin content was seen with carvone. Increase in lipophilicity of terpenes showed increase in flux, cumulative amount (Q(24)), and enhancement ratio which was significant with P < 0.000. But lag time was decreased and no correlation was found between lipophilicity and skin content. Histological studies showed changes in dermis which can be attributed to disruption of lipid packing of stratum corneum due to effect of nerolidol within lipid lamellae. It was found that small alcoholic terpenes with high degree of unsaturation enhance permeation of hydrophilic drugs, liquid terpenes enhance better than solid terpenes and terpenes with high lipophilicity are good penetration enhancers.